Rentabilidad de limón mexicano (Citrus aurantifolia Swingle) en Apatzingán, Michoacán - Martínez García, Jocelin (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The objective was to analyze the profitability of the Mexican lemon (Citrus aurantifolia swingle) during a productive cycle in the municipality of Apatzingán throughout the year 2021. The research was carried out through a case study and exploratory scope using the Political Analysis Matrix methodology and its indicators Being an exploratory type of research, there is an interest in examining the characteristics of the lemon production system for future research related to the economic and social approach. The research analysis was made up of 3 informant producers from the region, where average work was done through semi-structured interviews on production costs, prices paid day by day through the production system. The information collected was captured in a Microsoft Excel® database. Being a case study, specific and detailed information is obtained on how it works and the characteristics of each Mexican lemon production system of the producers. In the results, a positive profitability was obtained for the three producers, the growth that lemon production has been having in the municipality of Apatzingán where it represents 90% of the production of the state of Michoacán. The importance of the prices paid to the producer, since during the year 2021 it was an exponential year due to different factors such as pandemic, insecurity, climatic factors and changing markets.

El objetivo fue analizar rentabilidad del limón mexicano (Citrus aurantifolia swingle) durante un ciclo productivo en el municipio de Apatzingán durante todo el año 2021. La investigación fue realizada mediante un estudio de caso y de alcance tipo exploratorio mediante la metodología de Matriz de Análisis Política y sus indicadores. Al ser una investigación de tipo exploratoria se tiene interés en examinar las características del sistema productivo de limón para futuras investigaciones relacionadas con el enfoque económico y social. El análisis de la investigación se conformó mediante 3 productores informantes de la región, donde se trabajó por medio de entrevistas semi estructuradas sobre los costos de producción, precios pagado día a día a través del sistema de producción. La información recolectada fue capturada en una base de datos de Microsoft Excel®. Al ser un estudio de caso se obtiene una información específica y detallada sobre cómo funciona y las características de cada sistema de producción de limón mexicano de los productores. En los resultados, se obtuvo una rentabilidad positiva para los tres productores, el crecimiento que ha ido teniendo la producción de limón en el municipio de Apatzingán representa el 90% de la producción del estado de Michoacán. La importancia de los precios pagados al productor, ya que durante el año 2021 fue un año exponencial por diferentes factores como la pandemia, inseguridad, factores climáticos y mercados cambiantes.
Instituto de Investigaciones Agropecuarias y Forestales. Maestría en Producción Agropecuaria
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2024-1031; Agronegocios; Rentabilidad privada; Costos; Productores; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18841